Implementasi Sistem Manajemen Mutu Berbasis Nilai Islam Dalam Upaya Pembentukan Akhlak Santri - Muhammad Habib Imroni (Mathematics Education Study Program, 2025)
This study aims to identify, analyze, and evaluate the implementation of an Islamic value-based quality management system at the Sunan Ampel Banyuwangi Islamic Boarding School and reveal its impact on the formation of santri character. This objective is based on the need to understand how Islamic values are translated into effective quality management practices, which not only improve the quality of education but also shape the character of santri in accordance with Islamic teachings. This research uses a qualitative approach with a case study design. Data were collected through in-depth interviews, participatory observation and documentation. Informants were selected by purposive sampling, consisting of pesantren administrators, teachers, and students. Data analysis used interactive techniques, involving reduction, presentation, and conclusion drawing. Triangulation of methods was carried out to ensure data validity and identify patterns of Islamic value relationships in the formation of santri morals. The results showed that the Sunan Ampel Banyuwangi Islamic Boarding School has successfully integrated Islamic values in the quality management system, which not only improves the quality of education but also forms superior santri characters. The application of values such as honesty, responsibility, and ihsan through programs such as routine muhasabah and Islamic-based evaluation creates an Islamic educational environment. The strategy of forming santri morals, which involves daily activities such as dhikr, congregational prayers, and book studies, plays an important role in shaping character and discipline. The active involvement of stakeholders-nurturers, teachers, parents, and the community-creates a synergy that strengthens Islamic values in education and builds a harmonious relationship between the pesantren and its community. This approach is an effective model in creating a quality and character Islamic education institution.